An evaluation of modelling approaches and column removal time on progressive collapse of building. (February 2019) - Stephen, David; Lam, Dennis; Forth, John; Ye, Jianqiao; Tsavdaridis, Konstantinos Daniel
Abstract: Over the last few decades, progressive collapse disasters have drawn the attention of codified bodies around the globe; as a consequence, there has been a renewed research interest. Structural engineering systems are prone to progressive collapse when subjected to abnormal loads beyond the ultimate capacity of critical structural members. Sudden loss of critical structural member(s) triggers failure mechanisms which may result in a total or partial collapse of the structure proportionate or disproportionate to the triggering event. Currently, researchers adopt different modelling techniques to simulate the loss of critical load bearing members for progressive collapse assessment. GSA guidelines recommend a column removal time less than a tenth of the period of the structure in the vertical vibration mode. Consequently, this recommendation allows a wide range of column removal time which produces inconsistent results satisfying GSA recommendation. A choice of a load time history function assumed for gravity and the internal column force interaction affects the response of the structure. This paper compares different alternative numerical approaches to simulate the sudden column removal in frame buildings and to investigate the effect of rising time on the structural response.